Buenas prácticas ambientales para el recurso agua en la hostería “El Descanso del Toro” de la parroquia Vilcabamba - Espinosa Ramón, Rosa Teresa (2025)
Some authors agree that tourists consume more water than residents, therefore, the lack of good practices in the consumption of this resource would considerably affect the development of tourism, especially in areas where this is the case. Therefore, the need to carry out a research, whose general objective was: to propose good environmental practices for the responsible consumption of water in the “El Descanso del Toro” inn in the Vilcabamba parish, which is achieved by meeting two specific objectives: estimate the water consumption of the “El Descanso del Toro” inn and the residents of the Vilcabamba parish; and, propose measures for the efficient management of water in the inn, whose methodology used for the first objective was direct observation in the field, application of interviews, surveys and formulas used to calculate water consumption per resident taking the overcrowding index, and per tourist per capita, taking into account the total number of nights of occupancy in the year, average stay and average consumption in liters/tourist/day, determining the total water consumption with respect to the areas of the inn and the results of the surveys. . . For the second objective, we started from the data obtained from the first objective and the bibliographic review of similar studies. As a result of the first objective, it was obtained that the water consumption per tourist per day is 1404,83 liters and the water consumption per resident per day is 122.07 liters. "For the second objective, a manual of measures for efficient water resource management at the inn was proposed. In conclusion, inappropriate habits in water consumption, being part of tropical countries and the number of activities, that tourists carry out in inns induce greater water consumption than residents.